Medication-Related Needs and Humanistic Impact of Patient-Centered Pharmaceutical Care at University of Gondar Comprehensive Specialized Hospital, North-West Ethiopia - Abdela OA; Abay E; Beka S; Mengistie B; Ayalew MB (Dove Medical Press, 2020)
Ousman Abubeker Abdela,1 Enathun Abay,2 Senait Beka,3 Biset Mengistie,2 Mohammed Biset Ayalew1 1Department of Clinical Pharmacy, School of Pharmacy, College of Medicine and Health Science College, University of Gondar, Gondar, Ethiopia; 2School of Pharmacy, College of Medicine and Health Science, University of Gondar, Gondar, Ethiopia; 3Axum Pharmacy, Addis Ababa, EthiopiaCorrespondence: Ousman Abubeker Abdela Tel +251-912-02-3692Fax + 251-058-114 1240Email ousmy2009@gmail.comPurpose: To assess patients’ medication-related needs and the humanistic impact of patient-centered pharmaceutical care.Patients and Methods: A hospital-based cross-sectional study was conducted using self-administered structured questionnaires from February 4 to 28, 2019, on patients attending ambulatory care for chronic non-communicable diseases at the University of Gondar specialized teaching hospital, North-west Ethiopia. Data were entered to SPSS version 22 for analysis. Descriptive statistics was used to describe the socio-demographic characteristics and medication-related needs of study participants. Independent sample t-test and one-way ANOVA analysis were performed to check for possible associations between dependent and independent variables.Results: Information about what to do if patients missed doses and the potential side-effects or abnormal conditions caused by the prescribed medicines were not explained for most of the 425 patients studied. The majority of the study participants reported that they felt worried about adverse medicine effects, drug interactions, and long-term medicine use. Patients who were older than 50 or those receiving two or more medications were less satisfied with the effect of their medicine as compared to younger ones and those on monotherapy, respectively. People who were illiterate or had attended only primary schools thought that they received less disease and medicine information from health professionals than people who attended tertiary education.Conclusion and Recommendation: Most of the participants were particularly unhappy with the amount of information received about side-effects and what to do if doses were missed. Special emphasis should be given to patients with a low level of education as they were not satisfied with medicine and disease information obtained from health professionals, experienced more psychological impacts of medicine use, and had poor overall quality-of-life.Keywords: Ethiopia, pharmaceutical care, humanistic outcome, medication-related needs